The The Impact of the Technology Acceptance Model on Interest in Using QRIS for FEBI Students at IAIN Ponorogo - Jihan Arlista Putri; Rokamah, Ridho (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Interest in using payment systems, especially QRIS, has grown rapidly among students. New technology such as QRIS is a symbol of society's adaptation to technological advances in meeting increasingly complex and dynamic payment needs. The problem studied in this study is to find out the Technology Acceptance Model (TAM) affects the interest in using QRIS in FEBI IAIN Ponorogo students . This research method uses a descriptive quantitative approach with multiple linear regression analysis. The results showed that perceived usefulness, perceived ease of use, user attitudes and actual technology users had positive and significant results on interest in using QRIS. Meanwhile, risk perception has negative and significant results on interest in using QRIS